Measuring hours worked in Germany – Contents, data and methodological essentials of the IAB working time measurement concept - Susanne Wanger; Roland Weigand; Ines Zapf (Journal for Labour Market Research, 2016)
This article presents the Working Time Measurement Concept of the Institute for Employment Research, which determines the hours worked in Germany and their individual components. The Working Time Measurement Concept is the key data product on working time in Germany and underlies the German national accounts figure on labour input. These statistics on hours worked are essential for a proper analysis of aggregate labour market trends and cyclical fluctuations. In the Working Time Measurement Concept, changes in working hours due to collective agreements and economic fluctuations are brought together with shifts in employment structure, thus producing a differentiated picture of the scope, structure and development of the annual working time of gainfully employed persons. We outline the conceptual and methodological framework of the measurement, which continually evolves due to its integration in the system of national accounts and due to innovations to the statistical procedures applied. An overview of single components and their data sources is given, while the resulting time series of hours worked and the volume of work are depicted according to their long run trends, cyclical variation and reaction in the 2008/09 financial and economic crisis.
Keywords: C82; E01; J2; 330; IAB-Arbeitszeitrechnung - Methode; Arbeitszeit; Arbeitsvolumen